Development of Innovative Learning Model in Madrasah Ibtidaiyah Teacher Education Study Program - Rivas , Pablo; Klügl , Franziska (ELEMENTARY : Journal of Primary Education, 2024)
This research aims to develop an innovative learning model in the Madrasah Ibtidaiyah Teacher Education Study Program using qualitative methods. This innovative learning model is expected to improve teaching effectiveness and the quality of education for prospective madrasah ibtidaiyah teachers. The research involved in-depth interviews with lecturers and students, as well as observation of learning practices in the study program. The results of this study show that the implementation of an innovative learning model that includes the use of educational technology, project-based learning methods, and active learning approaches can have a positive impact in improving student engagement and learning outcomes. The model also emphasizes the importance of collaboration between lecturers and students as well as the integration of character values in the learning process. The findings of this study are expected to be a reference for curriculum development and learning strategies in the madrasah ibtidaiyah teacher education study program and contribute to improving the quality of education in the institution.